Aspectos distintos da paixão da nostalgia na construção dos sujeitos dos enunciados nas canções de Nando Reis - Silva, Lilian Maria Marques e (Estudos Semióticos, 2008)
The different manifestations of nostalgia passion, now true, then false, many times, punctual, based on the Greimassian semiotics theory, is our object of study in the songs “Pra ela voltar”, “Mesmo sozinho” and “N”, written and interpreted by Nando Reis.